Caffeine Consumption and Perceptions of Medical Students; A Cross Sectional Study - Ur Rehman, Ibad; Tahir, Dawood; Zahra, Tatheer; lee, Ka Yiu (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Objective: This study is aimed to identify the relationships between caffeine consumption and perceptions of medical students. Methodology: This is a cross sectional study, conducted over 5 months in year 2020 in a Medical University in Islamabad, Pakistan. Participants completed a questionnaire which assesses patterns of caffeine consumption, and perceived benefits and adverse effects. Spearman correlation was used to identify their relationships. This study is being reported in adherence to STROBE reporting guidelines. Results: A total of 101 participants were recruited, of which 77.2% reported to consume caffeine. Results showed significant associations between caffeine consumption and self-reported addiction (rho=0.329, p=0.001), perceived adverse effects including weight gain (rho=0.262, p=0.008) and palpitations (rho=0.210, p=0.035),and perceived benefits such as improved academic performance (r=0.334, p=0.001), increased recalling power(rho= 0.283, p = 0.004) and increased reading power(rho=0.359, p=0.000). Caffeine consumption was also associated with self-reported academic load or stress (rho=0.491, p=0.000). Conclusion: Although the majority of medical students were aware of the harmful effects of caffeine consumption, most of them were consuming caffeine. More education is needed to increase the awareness among medical students. Keywords: Caffeine, Medical students, addiction, stress, awareness, diet